Comparison of 0.2% chlorhexidine gel and 10% betadine on healing of tooth socket in mice - Ali Peimani; Samaneh Keshavarz; Tahareh Eslammanesh; Mahmoud Sheikh Fathollahi (Mashhad University of Medical Sciences, 2017)
Introduction: Tooth extraction is the most common surgical procedure performed in dental office. Various drugs are used to accelerate wound healing in soft and bone tissues.In this study, the effect of 0.2% chlorhexidine gel and 10% betadine gel on tooth socket healing was investigated. Materials and Methods: This experimental study was performed on 45 male mice randomly divided into three groups of 15. Under general anesthesia, the right maxillary second molar of all of the mices were extracted. The socket of the first group was covered with 0.2% chlorhexidine gel and the second group was covered with 10% betadine gel, and the socket of third group was left empty. On the third, seventh and fourteenth days after surgery, one third of the animals were sacrificed from each group. Then the prepared slides from each group were examined. Results: The extent of granulation tissue on the third day after tooth extraction in the chlorhexidine group was greater than the remaining two groups.. The number of lymphocyte on the seventh day after tooth extraction in the chlorhexidine group were lower than the control group. The number of macrophage on the 14th day after tooth extraction in the chlorhexidine and betadine groups was lower than the control group. The number of fibroblasts in the chlorhexidine group on the 14th day after tooth extraction were higher than the control group. These differences were statistically significant. Conclusion: According to the results of this study, 0.2% chlorhexidine gel can accelerate the process of tooth socket healing.